2016
DOI: 10.1155/2016/6257071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Radiation on Unsteady MHD Free Convection Flow of Jeffrey Fluid over a Vertical Plate with Ramped Wall Temperature

Abstract: Influence of thermal radiation on unsteady magnetohydrodynamic (MHD) free convection flow of Jeffrey fluid over a vertical plate with ramped wall temperature is studied. The Laplace transform technique is used to obtain the analytical solutions. Expressions for skin friction and Nusselt number are also obtained. Results of velocity and temperature distributions are shown graphically for embedded parameters such as Jeffrey fluid parameterλ, Prandtl numberPr, Grashof numberGr, Hartmann numberHa, radiation parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…An investigation was executed by Narahari et al to observe the fluid flow with a heated wall for an infinite vertical plate [32]. Khan's work [33] on the MHD flow of a Jeffery fluid was extended by Zin et al [34] for ramped wall temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation was executed by Narahari et al to observe the fluid flow with a heated wall for an infinite vertical plate [32]. Khan's work [33] on the MHD flow of a Jeffery fluid was extended by Zin et al [34] for ramped wall temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chandran et al [20] used the ramped wall temperature condition with convective viscous fluid flow. Some researches taking into account the ramped temperature conditions can be found in the recent literature [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chandran et al [31] observed the variation in momentum boundary layer thickness subjected to ramped temperature condition. Zin et al [32] extended the study of Khan [33] on MHD flow of Jeffery fluid for ramped wall temperature. Maqbool et al [34] further extended this work for ramped wall velocity condition to examine the significance of simultaneous boundary conditions.…”
Section: Introductionmentioning
confidence: 99%